Large signal analysis of the electroabsorption modulator - Abuelma’atti, M.T. (2004)
Large signal analysis of the electroabsorption modulator driven by a multisinusoidal RF signal is presented. The special case of a two-tone equal-amplitude RF signal is considered in detail, and the results are compared with previously published results.